Demand Articulation of Emerging Technologies Investigating the Longitudinal Dynamics of Innovation. - Kodama, Fumio (Cambridge Scholars Publisher, 2019)
In today's high-tech environment, we have to conceptualize a sophisticated translation skill that converts a vague set of wants into well-defined products. To do so, we must come to the concept of ""demand articulation."" Marketing scholars have summarized that this concept is an important competency of market-driving firms. Most firms are more comfortable in a world of pre-articulated demand, wherein customers know exactly what they want, but the firm's challenge is to unearth that information. In order to better understand this idea, the book is organized into five categories, providing vario.